Plasticity of GluN1 at Ventral Hippocampal Synapses in the Infralimbic Cortex - Castillo-Ocampo, Yesenia; Colón, María; Hernández, Anixa; Lopez, Pablo; Gerena, Yamil; Porter, James T. (Frontiers in Synaptic Neuroscience, 2021)
Although the infralimbic cortex (IL) is not thought to play a role in fear acquisition, recent experiments found evidence that synaptic plasticity is occurring at ventral hippocampal (vHPC) synapses in IL during auditory fear acquisition as measured by changes in the NMDA receptor-mediated currents in male rats. This electrophysiological data suggests that fear conditioning changes the expression of NMDA receptors on vHPC-to-IL synapses. To further evaluate the plasticity of NMDA receptors at this specific synapse, we injected AAV particles expressing channelrhodopsin-EYFP into the vHPC of male and female rats to label vHPC projections with EYFP. To test for NMDA receptor changes in vHPC-to-IL synapses after fear learning, we used fluorescence-activated cell sorting (FACS) to quantify synaptosomes isolated from IL tissue punches that were positive for EYFP and the obligatory GluN1 subunit. More EYFP+/GluN1+ synaptosomes with greater average expression of GluN1 were isolated from male rats exposed to auditory fear conditioning (AFC) than those exposed to context and tones only or to contextual fear conditioning (CFC) suggesting that AFC increased NMDA receptor expression in males. In a second experiment, we found that pairing the tones and shocks was required to induce the molecular changes and that fear extinction did not reverse the changes. In contrast, females showed similar levels of EYFP+/GluN1+ synaptosomes in all behavioral groups. These findings suggest that AFC induces synaptic plasticity of NMDA receptors in the vHPC-to-IL projection in males while female rats rely on different synaptic mechanisms.